Multi - Level Marketing: An Economic Model - Richey, Jeremiah; Kang, Bohyeon (Indian Journal of Marketing, 2015)
This paper developed a simple economic model of multi-level marketing that captured two fundamental aspects of the intrinsic structure of multi-level marketing: (a) sequential entrance into the market, and (b) the lack of information on the number of competing sellers. The sequential aspect of entrance into the market leads to "the first mover bias." This leads to initial entrants' capturing large surpluses and removes the incentive for latter entrants to enter the market, resulting in less than full market penetration under complete information. The lack of information on the competing sellers, mixed with a signaling mechanism and an upstream commission for recruitment, creates an incentive to send false signals. This leads to entrants with resulting negative profits. Depending on the parameters of the model, this can lead to a very large percentage of participants to be negative earners with a small percentage reaping large rewards. These results indicate that stricter discloser laws regarding the number of participants and their earnings should be considered. Furthermore, if such laws are enforced, multilevel marketing firms will need to seek alternative payment schemes to ensure market saturation of their products.